2020
DOI: 10.3390/jmse8100798
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Stochasticity of Waves on Coastal Flood and Its Variations with Sea-level Rise

Abstract: Coastal floods are driven by many hydro-meteorological forcing factors, among which are mean sea levels, tides, atmospheric storm surges, and waves. Depending on these conditions, wave overtopping may occur and, in some cases, lead to a significant flood. In the present study, we investigate the effect of the stochastic character of waves on the flood itself using a phase-resolving wave model (SWASH). We focus on the macro-tidal site of Gâvres (France), consider two past flood events (both resulting from wave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
0
14
2
Order By: Relevance
“…13) whatever the time horizon. This result differs from the one of Idier et al (2020b), who showed the importance of this effect that was there comparable to the one of SLR as long as the still water level remains smaller than the critical level above which overflow occurs. The differences between both studies may be explained by the differences in the procedure.…”
Section: Wave Stochasticitycontrasting
confidence: 96%
See 2 more Smart Citations
“…13) whatever the time horizon. This result differs from the one of Idier et al (2020b), who showed the importance of this effect that was there comparable to the one of SLR as long as the still water level remains smaller than the critical level above which overflow occurs. The differences between both studies may be explained by the differences in the procedure.…”
Section: Wave Stochasticitycontrasting
confidence: 96%
“…A global flooding indicator is defined as the total water volume Y that has entered the territory at the end of the simulation. To account for the random character of waves, the modelling of the coastal flood induced by overtopping processes is combined with a random generation of wave characteristics in SWASH as described by Idier et al (2020b). For given offshore forcing conditions, the simulation is repeated 20 times, and the median value (denoted Q50) of Y is calculated as well as the quartiles (25 th and 75 th percentiles, respectively denoted Q25 and Q75).…”
Section: Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In the framework of the present study, we follow the last approach mentioned above and use the non-hydrostatic phase-resolving model SWASH [4,36] to model floods at the study site (Figure 1b). The modelling chain was previously set up by [6,7]. We briefly summarise the key elements here.…”
Section: Process-based Model Setup and Validationmentioning
confidence: 99%
“…Floods can be induced by overflow (when the total water level, including the wave setup, exceeds the coastal defence crests) and wave overtopping. Owing to the significant progress achieved in numerical hydrodynamic models (especially phase-resolving models, e.g., Simulating Waves till Shore (SWASH), [4]), it is now possible to precisely reproduce floods, even in the case of wave overtopping (see, e.g., [5][6][7]).…”
Section: Introductionmentioning
confidence: 99%